The tasks of a speech therapist in the context of work on the correct pronunciation of sounds - Makhmudova Madinaxon Sobirxonovna; Toshmatova Zumradxon (Genius Journals, 2025)
The article discusses the tasks of a speech therapist in the context of work on the correct pronunciation of sounds, the development of speech listening skills, the development of the articulation apparatus, and the development of speech breathing
Keywords: grammatical skills; speech forms